IMPLEMENTASI DOKUMEN DESIDERIO DESIDERAVI BAGI FORMASIO LITURGI UMAT BERIMAN - Lontoh, Raymond Christoforus; Pondaag, Stenly Vianny (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
This article aims to discuss the implementation of liturgical formation according to papal document Desiderio Desideravi. The data collection method used is document and literature study. The author examines various views regarding liturgical formation contained in various Church documents, then outlines the important points. In this article, two forms of liturgical formation are explained. The first form of formation is formation for liturgy which is carried out through academic channels: teaching, catechesis and training. The second form of formation is formation through liturgy, which emphasizes the active participation aspect of the entire congregation. In other words, formation through the liturgy means that the liturgy forms the faithful. The main subjects of liturgical formation are lay people, seminarians and priests.